(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the total protein content in the stem, grain and bean of the plant Indigofera tinctoria L., belonging to the legume family (Fabaceae), grown in three different (fertile, saline, arid) climatic conditions of the Fergana region. The Keldal method is used in the work – one of the generally recognized methods for determining the total protein content in the plant Indigofera tinctoria L. When determining the amount of protein in the samples by the Keldal method, the stages of hydrolysis with sulfuric acid, neutralization with sodium hydroxide and titration of the remaining acid with an alkali solution were carried out. The results obtained were compared with each other and with the amount of protein from other legumes. According to the results of the study, it was found that the grain of Indigofera tinctoria L. grown in arid conditions contains 25.967% protein, in the fruit box - 9.539%, in saline conditions - in the stem of the plant - 5.688%.